Construct validation and reliability of self-efficacy to the condom use scale on college Mexican students - Huitzil-Ascención, Ana Lleli; Landeros-Olvera, Erick; Benavides-Torres, Raquel; Linares-Fleites, Gladys; Villa-Rueda, Alma; Morales-Rodríguez, Claudia (Acta Universitaria, 2016)
Sexual transmission infections are public health problems, the absence of instruments to measure condom use’s skills is an urgent need as a preventive measurement. The aim of this work is to translate, adapt, and test validity and reliability of self-efficacy scale of condom use (EAEPUC, for its acronym in spanish) (Dilorio, Maibach, O’Leary, Sanderson & Celentano, 1997). Scale validation process consisted of: translation, back translation, expert analysis, pilot application and at the end an exploratory and confirmatory factor analysis were performed (AFC and AFC). To reinforce results a comparative design test / re-test was where self-efficacy (AE) was measured by sex for condom use in 217 college students of both sexes (60.8% women, age 21 ± 1.20 years). Expert analysis showed a Content Validity Index of 8.42. In AFE, six factors explained 58.6% of variance, a Chi2 = 679.035 resulted in AFC, p < 0.05, CFI = 0.836, SRMR = 0.073. When making comparisons by gender, no statistically significant differences in test were observed (M = 79.8 ± 12.9 vs. 76.3 ± 13.1  p = 0.058), and re-test neither (M = 81.05 ± 14.7 vs. 80.1 ± 13.06,  p = 0.652). Overall Cronbach Alpha coefficients test and re-test were very similar (0.868 and 0.849 respectively), thus results give scale a stable and acceptable internal consistency. EAEPUC was translated and adapted to Spanish, it is preliminarily valid and reliable in college students, however it requires study replicas to promote their external validation.
Keywords: Array; Array; Array; Array